Assessment of Consumer Knowledge of Gluten-Free Food - Piec, Karolina; Janczar-Smuga, Małgorzata (Ocena wiedzy konsumentów na temat żywności bezglutenowej, 2022)
The gluten-free food market has become one of the fastest-growing food markets for food intolerances. People with celiac disease, gluten intolerance, non-celiac gluten sensitivity, and other gluten-related diseases should follow a gluten-free diet. The demand for gluten-free products is growing yearly, mainly due to the increasing number of diagnosed cases. The aim of the study was to assess consumers’ knowledge of gluten-free foods and covered people of all ages, and was conducted using a questionnaire. The research results indicate that most consumers have a lot of knowledge concerning gluten-free food. Moreover, most consumers know what gluten is and what products to avoid while on a gluten-free diet. They also know which diseases it causes and that it is necessary to follow a diet, but they have difficulty determining the acceptable gluten content in gluten-free products. Consumers’ most crucial parameter when choosing a gluten-free product is taste. The results of the survey also show that a gluten-free diet is more popular among women than men.
Nauki Inżynierskie i Technologie = Engineering Sciences and Technologies, 2022, Nr 38, s. 164-185